The compliance of contractor on providing the occupational safety system at the construction site. (Case Study - Government Projects) / Zakaria Yaa'cob, Mohamad Sohaimi Man and Dr. Md. Yusof Hamid - Yaa'cob, Zakaria; Man, Mohamad Sohaimi; Hamid, Md. Yusof (Dr.) (2011)
Now day we seen many accidents happen at the construction site, it seen is in control situation. The contract that stated the need of safety at construction site and it like the contractor did not take a serious action on it. All parties involved in the project must contribute their roles in resolving the problems. It must be study according to law and regulation such as Occupational Safety and Health Act 1974 and Machinery and Industry Act 1967 and providing the safety management system by contractor. There are two methodologies that has been used in this research, one is the literature review including safety management system, such as safety policies, safety plan, accident reporting system, training, monitoring and supervising and risk assessment, legislation. The second methodology is to do a case study on government projects by using interview to the target group that is contractor, members of professional, and safety officer. The analysis base on the finding of case study for every item discuss and the result of the analysis will show the compliance of contractor on providing the safety management system. As Conclusion, at the end of this research, a proposal to government agencies for an improvement of system at construction site.